Implementação da educação integral em tempo integral nas escolas municipais de São Leopoldo - RS - Carpes, Fabiane (Universidade do Vale do Rio dos Sinos, 2025)
This dissertation aimed to analyze the implementation of the full-time integral education policy in the municipal education network of São Leopoldo based on national guidelines. The research was motivated by the author's experience as a school administrator at EMEF Paulo Beck, a school where the process of extending school hours began in 2022. The study sought to understand how this policy has been applied in municipal schools. To this end, challenges, adopted practices, and the relationship between national guidelines and school organization were identified. The investigation followed a qualitative approach, based on document analysis and semi-structured interviews. The results indicated that the implementation of full-time integral education in the municipal schools of São Leopoldo occurs without a structured municipal policy, leading each institution to develop its own strategies to meet local demands. The intervention proposal resulting from this research was the development of guidelines that could contribute to the creation of a municipal policy. Finally, it was concluded that there is a need for a clear and well-founded municipal policy to ensure the continuity and expansion of this educational model in the municipality.
Keywords: Política educacional; Educação integral; Tempo integral; Educational policy; Integral education; Full-time education; ACCNPQ::Ciências Humanas::Educação